2014
DOI: 10.1523/jneurosci.0381-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Synaptopodin Regulates Spine Plasticity: Mediation by Calcium Stores

Abstract: The role of synaptopodin (SP), an actin-binding protein residing in dendritic spines, in synaptic plasticity was studied in dissociated cultures of hippocampus taken from control and SP knock-out (SPKO) mice. Unlike controls, SPKO cultures were unable to express changes in network activity or morphological plasticity after intense activation of their NMDA receptors. SPKO neurons were transfected with SP-GFP, such that the only SP resident in these neurons is the fluorescent species. The localization and intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
114
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 25 publications
9
114
1
Order By: Relevance
“…Synaptopodin (SP; Mundel et al, 1997;Asanuma et al, 2005) was recognized to be a marker (Deller et al, 2000) and essential component of the SA (Deller et al, 2003). SP-deficient mice lack SAs (and COs; Bas and show deficits in synaptic plasticity (Deller et al, 2003;Jedlicka et al, 2009;Zhang et al, 2013;Vlachos et al, 2013a;Korkotian et al, 2014). Meanwhile, experimental evidence has been provided that SP/SA Ca 2+ stores regulate different forms of synaptic plasticity: (1) RyR-dependent long-term potentiation (LTP) of synaptic strength was reported (Vlachos et al, 2009), as well as (2) mGluR-triggered IP3R-mediated synaptic depression, i.e., long-term depression (LTD) of excitatory synaptic strength (Holbro et al, 2009).…”
Section: The Sa Controls Different Forms Of Synaptic Plasticitymentioning
confidence: 99%
“…Synaptopodin (SP; Mundel et al, 1997;Asanuma et al, 2005) was recognized to be a marker (Deller et al, 2000) and essential component of the SA (Deller et al, 2003). SP-deficient mice lack SAs (and COs; Bas and show deficits in synaptic plasticity (Deller et al, 2003;Jedlicka et al, 2009;Zhang et al, 2013;Vlachos et al, 2013a;Korkotian et al, 2014). Meanwhile, experimental evidence has been provided that SP/SA Ca 2+ stores regulate different forms of synaptic plasticity: (1) RyR-dependent long-term potentiation (LTP) of synaptic strength was reported (Vlachos et al, 2009), as well as (2) mGluR-triggered IP3R-mediated synaptic depression, i.e., long-term depression (LTD) of excitatory synaptic strength (Holbro et al, 2009).…”
Section: The Sa Controls Different Forms Of Synaptic Plasticitymentioning
confidence: 99%
“…Imaging was conducted as detailed elsewhere (Korkotian et al, 2014;Cohen et al, 2008). Glass coverslips containing the cultures were incubated for 1 h at room temperature with the standard recording medium (in mM, 129 NaCl; 4 KCl; 2 CaCl 2 ; 1 MgCl 2 ; 10 Glucose; 10 HEPES; pH 7.4, 320 mOsm), containing 2 mM Fluo-2 High Aff (AM) (TEFLabs, USA).…”
Section: Calcium Imaging and Analysismentioning
confidence: 99%
“…Cells were transfected with green fluorescent protein (GFP) at the age of 7 days in vitro, using lipofectamine 2000 (Korkotian et al, 2014). Control and 1% ethanol-treated cells were fixed with 4% paraformaldehyde at the age of 14-21 days in vitro, and individual neurons were imaged on the stage of a confocal microscope, 3D reconstructed, and analyzed morphologically in a blind procedure.…”
Section: Imaging Of Cell Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…This study follows our interest in the role of calcium stores in spine plasticity, where we found that dendritic spines contain ryanodine receptor-type calcium stores. 5 In the more recent study, 6 we employed plasmids that encode the Orai1 protein, as well as plasmids that encode the dominant negative (DN) Orai1. We also knocked down Orai1, using selective siRNA for this protein.…”
mentioning
confidence: 99%